Sex Differences in Bipolar Disorders: Impact on Psychopathological Features and Treatment Response - Menculini, Giulia; Steardo, Luca; Sciarma, Tiziana; D'Angelo, Martina; Lanza, Laura; Cinesi, Gianmarco; Cirimbilli, Federica; Moretti, Patrizia; Verdolini, Norma; De Fazio, Pasquale; Tortorella, Alfonso (Frontiers in Psychiatry, 2022)
Introduction Sex differences were demonstrated in bipolar disorders (BD) concerning epidemiological, clinical, and psychopathological characteristics, but consensus is lacking. Moreover, data concerning the influence of sex on treatment response in BD is contrasting. The present cross-sectional study aimed to analyze sex differences in a population of BD subjects, with specific focus on psychopathological features and treatment response. Materials and Methods Subjects diagnosed with BD according to the Diagnostic and Statistical Manual of Mental Disorders, 5th version (DSM-5) were recruited. Socio-demographic and clinical characteristics were collected. The Hamilton Rating Scale for Depression, the Mania Rating Scale (MRS), the brief version of the Temperament Evaluation of Memphis, Pisa and San Diego—Münster version (briefTEMPS-M), and the Barratt Impulsiveness Scale−11 items (BIS-11) were used for psychopathological assessment. Treatment response was appraised with the Alda Scale. We performed bivariate analyses to compare socio-demographic, clinical, and psychopathological characteristics between men and women (p < 0.05). A logistic regression was run to analyze features that were significantly associated with female sex. Results Among the recruited 219 BD subjects, 119 (54.3%) were females. Women had a lower scholarity (p = 0.015) and were less frequently employed (p = 0.001). As for psychopathological features, a higher MRS total score (p < 0.001) was detected among women, as well as higher BIS-11 total score (p = 0.040), and briefTEMPS-M score for anxious temperament (p = 0.006). Men showed higher prevalence of DSM-5 mixed features (p = 0.025), particularly during a depressive episode (p = 0.014). Women reported longer duration of untreated illness (DUI) (p < 0.001). There were no sex differences in the Alda Scale total score when considering the whole sample, but this was significantly higher among men (p = 0.030) when evaluating subjects treated with anticonvulsants. At the logistic regression, female sex was positively associated with longer DUI (p < 0.001; OR 1.106, 95% CI 1.050–1.165) and higher MRS total score (p < 0.001; OR 1.085, 95% CI 1.044–1.128) and negatively associated with employment (p = 0.003; OR 0.359, 95% CI 0.185–0.698) and DSM-5 mixed features (p = 0.006; OR 0.391, 95% CI 0.200–0.762). Conclusions The clinical presentation of BD may differ depending on sex. The severity of BD should not be neglected among women, who may also display worse treatment response to anticonvulsants.